The Utilization of Oil Palm Empty Fruit Bunches for Growth of Oyster Mushroom (Pleurotus ostreatus) and Biodelignification Process During Planting Cycle - Firda Dimawarnita; Urip Perwitasari; Sidik Marsudi; Yora Faramitha; Suharyanto Suharyanto (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
Indonesia produces a large amount of oil palm empty fruit bunch (EFB) that has potency used as media for mushroom cultivation. The research emphasized the use of EFB to grow oyster mushrooms as an alternative for delignification without chemicals. This research aimed to study the growth of oyster mushroom (Pleurotus ostreatus) at EFB based growing media treatments. The media consisted of a mixture of EFB and sawdust at the composition of 0%, 25%, 50%, 75%, and 100%. The media were also supplemented with rice bran, CaCO3, and TSP fertilizer. The data were collected on the mycelium growth and the mushroom weight. During cultivation in baglog, there was no difference in mycelium growth rate. The EFB composition of 25% showed faster growth among the other compositions, followed by the EFB composition of 50%, 75%, and 0%. The highest Biological Efficiency Ratio (BER) at 56.25% was obtained at media composition of 50%. The EFB contained in baglog also showed biodelignification process. Biodelignification has the benefit which can reduce the use of chemicals in the delignification process to convert EFB into cellulose. The highest lignin reduction (40.12%) occurred in 75% of EFB media composition, while hemicellulose (49.56%) occurred in 100% EFB media composition.